Menelaah Ijma Ulama tentang Crypto Currency dari Sudut Pandang Kaidah Muamalah Al-Aslu Fil Muamalah Ibahah - Purba, Asnan; Suntana, Ija; Anwar, Syahrul (Sharia Journal and Education Center Publishing, 2026)
The rapid development of blockchain technology and cryptocurrency has generated significant legal challenges within Islamic commercial law, particularly in determining the permissibility of digital financial instruments that were unknown in classical fiqh literature. This article aims to examine the legal status of cryptocurrency based on the fiqh maxim al-aslu fil muamalah ibahah and to analyze the implications of the ulama consensus established during the 2021 Ijtima’ Ulama of the Indonesian Council of Ulama (MUI). This study employs a normative legal research method using conceptual, typological, and comparative approaches. Cryptocurrency is systematically categorized into five types: utility tokens, security tokens, asset-backed tokens, decentralized finance (DeFi) tokens, and non-fungible tokens (NFTs), each analyzed through definitional, operational, sharia compliance, and ijma-based perspectives. The findings demonstrate that cryptocurrency cannot be assessed through a generalized legal judgment but must be evaluated differentially according to its function, characteristics, and underlying assets. Utility tokens and security tokens may be considered permissible when they fulfill the requirements of lawful commodities, provide tangible benefits, and avoid elements of gharar, maysir, and riba. In contrast, purely speculative cryptocurrencies lacking clear utility or asset backing tend to conflict with Islamic legal principles. This study affirms the continued relevance of al-aslu fil muamalah ibahah as a methodological framework for addressing contemporary digital financial innovations while maintaining adherence to maqasid al-shariah and legal prudence.